PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPA DI SDN INPRES DALAKA - Rahmawaty Rahmawaty (Koordinat Jurnal MIPA, 2022)
Low learning outcomes are a manifestation of various problems that arise from learning activities. Low learning outcomes in science subjects are indicated by results that are below the Minimum Completeness Criteria (KKM). Based on the results of observations, the method used is in the form of lectures, discussions and practicals, but the results are not optimal. Students tend to be passive, only a few are actively participating in learning. Based on these problems, the author made efforts to improve the science learning outcomes of the fifth grade students of SDN Inpres Dalaka for the 2020/2021 academic year by applying the TGT learning model. This research is a quasi-experimental research. The purpose of this research is to improve learning outcomes in science subjects. Based on the results of the analysis, it was found that learning science by applying the TGT method could improve science learning outcomes. This is indicated by the difference in pretest and posttest scores. Where the posttest results are higher than the pretest results. This increase is an implication of increasing student learning activities. Students feel more enthusiastic about participating in learning.